A Tale of Two Electorates?: The 2021 Federal Election and the AfD Voter in East and West. Issue 2 (1st June 2022) - Hansen, Michael A.; Olsen, Jonathan
Abstract: Although the AfD is not, strictly speaking, an "eastern" party, its distinct electoral results in the two halves of Germany—underscored once again in the 2021 federal election—are something of a puzzle. In order to explain how and why the AfD performs better in eastern Germany than in western Germany, we analyze district-level results for the AfD vote, employing multiple regression models in order to find correlates with constituency vote share. We conclude that the only socio-demographic variable common to both eastern and western German AfD voters is their level of education. Significantly, we find that eastern AfD voters are both older and more economically secure than western German voters for the AfD.